The Development of Practice Recommendations for Drug-Disease Interactions by Literature Review and Expert Opinion - van Tongeren, Justine M. Z.; Harkes-Idzinga, S. Froukje; van der Sijs, Heleen; Atiqi, Roya; van den Bemt, Bart J. F.; Draijer, L. Willem; Hiel, Deline; Kerremans, Adrian; Kremers, Bart; de Leeuw, Marc; Olthoff, Marleen V.; Pham, T. Kim-Loan; et al. (Frontiers in Pharmacology, 2020)
Background: Drug-disease interactions negatively affect the benefit/risk ratio of drugs for specific populations. In these conditions drugs should be avoided, adjusted or accompanied by extra monitoring. The motivation for many drug-disease interactions in the Summary of Product Characteristics (SmPC) is sometimes insufficiently supported by (accessible) evidence. As a consequence the translation of SmPC to clinical practice may lead to non-specific recommendations for prescribers.. For the translation of this information to the real world, it is necessary to evaluate the available knowledge about drug-disease interactions, and to formulate specific recommendations for prescribers and pharmacists. The aim of this paper is to describe a standardized protocol how to develop practice recommendations for drug-disease interactions by literature review and expert opinion. Methods: Drug-disease interactions will be evaluated following a six-step plan, involving a multidisciplinary expert panel. (1) The scope of the drug-disease interaction will be specified by defining the disease and by describing relevant effects of this drug-disease interaction. Drugs possibly involved in this drug-disease interaction are selected by checking the official product information, literature and expert opinion. (2) Evidence will be collected from the official product information, guidelines, handbooks and primary literature. (3) Study characteristics and outcomes will be evaluated and presented in standardized reports, including preliminary conclusions on the clinical relevance and practice recommendations. (4) The multidisciplinary expert panel will discuss the reports and will either adopt or adjust the conclusions. (5) Practice recommendations will be integrated in clinical decision support systems and published. (6) The results of the evaluated drug-disease interactions will remain up-to-date by screening new risk information, periodic literature review and (re)assessments initiated by health care providers. Discussion: The procedure of a structured evaluation of drug-disease interactions is described. The advices will generate clinical decision support for healthcare professionals based on available evidence and expert opinion, which enables optimal patient care.